Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan: Studi Pada Perusahaan Pertambangan - Azhari Sofyan (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This study aims to examine the relationship between good corporate governance and firm value. Companies that implement good governance will experience a change in image and increase in company value. Good corporate governance is expected to present a balance between various interests that can realize profits for the company. The population in this study are mining companies listed on the Indonesia Stock Exchange, Philippine Stock Exchange, and Hanoi Stock Exchange in 2016-2020, totaling 82 companies. The sample selection technique in this study used a purposive sampling method, which met the research sample criteria, namely 72 companies during the 2016-2020 period. The results of the study show that the variables of managerial ownership, institutional ownership, and independent commissioners have a significant effect on the value of mining companies listed on the Indonesia Stock Exchange, the Philippines Stock Exchange, and the Hanoi Stock Exchange for the 2016-2020 period. However, the audit committee has no significant effect on the value of mining companies listed on the Indonesia Stock Exchange, Philippine Stock Exchange and Hanoi Stock Exchange for the 2016-2020 period.